Novel possible symmetries of S-matrix generated by Z2n-graded Lie superalgebras - Ren Ito; Akio Nago (Nuclear Physics B)
In this paper, we explore Z2n-graded Lie (super)algebras as novel possible generators of symmetries of S-matrix. As a result, we demonstrate that a Z2n-graded extension of the supersymmetric algebra can be a symmetry of S-matrix. Furthermore, it turns out that Z2n-graded Lie algebras appear as internal symmetries. They are natural extensions of the Coleman-Mandula theorem, which is the no-go theorem for generators of symmetries of S-matrix, and the Haag-Łopuszański-Sohnius theorem, which extends the Coleman-Mandula theorem to include superalgebras.